2008
DOI: 10.1002/sca.20130
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopic imaging of adipose tissue based on second‐harmonic generation and two‐photon excited fluorescence

Abstract: The fresh adipose tissue was investigated by the use of multiphoton microscopy (MPM) based on two-photon excited fluorescence and second-harmonic generation (SHG). Microstructure of collagen and adipose cells in the adipose tissue is clearly imaged at a subcellular level with the excitation light wavelengths of 850 and 730 nm, respectively. The emission spectrum of collagen SHG signal and NADH and FAD fluorescence signal can also be obtained, which can be used to quantify the content of collagen and adipose ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Two‐photon microscopy (TPM) imaging is currently a powerful and well‐established tool, as it provides rapid, real‐time, and noninvasive “optical biopsy” evaluation of tissue. Our previous studies have demonstrated that TPM technique can not only enable direct noninvasive visualization of the distribution of extracellular matrix components, but monitor the morphological and functional changes of cells, and good agreement was obtained between TPM image and the corresponding H&E staining image (Huang et al ., ; Chen et al ., ). Even so, for more objective and reliable pathologic diagnosis, it is essential to quantify morphological changes based on the TPM images.…”
Section: Introductionmentioning
confidence: 96%
“…Two‐photon microscopy (TPM) imaging is currently a powerful and well‐established tool, as it provides rapid, real‐time, and noninvasive “optical biopsy” evaluation of tissue. Our previous studies have demonstrated that TPM technique can not only enable direct noninvasive visualization of the distribution of extracellular matrix components, but monitor the morphological and functional changes of cells, and good agreement was obtained between TPM image and the corresponding H&E staining image (Huang et al ., ; Chen et al ., ). Even so, for more objective and reliable pathologic diagnosis, it is essential to quantify morphological changes based on the TPM images.…”
Section: Introductionmentioning
confidence: 96%
“…One previous study demonstrated the feasibility for visualization of adipocytes and collagen in adipose tissue by MPAM/SHGM. 13 That study showed adipocytes and collagen could be identified by MPAM and SHGM, respectively, but did not indicate the site of AT origin or status of obesity. Given the complex 3D architecture and makeup of AT and the potential role that the extracellular matrix may play in remodeling and function of this tissue, 14 methodologies that provide indication of spatial organization between AT constituents could be highly beneficial to the characterization of intact AT but also be used to better understand the changes associated with obesity and insulin resistance.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, two‐photon excited fluorescence (TPEF) microscopy has been applied to image tissue architecture and cellular morphology of unstained tissue samples in biomedical research (Chen et al ., ). This technique presents a non‐invasive and high‐resolution laser scanning enabling visualization of cellular and subcellular structures without any exogenous fluorescent agents while maintaining tissue viability (Zipfel et al ., ; Wilder et al ., ; Huang et al ., ). Compared with traditional optical imaging, TPEF microscopy has the advantages of deeper penetration depth, higher resolution, lower photo‐bleaching, and photo‐toxicity.…”
Section: Introductionmentioning
confidence: 97%